Is it just steps and calories? Elementary school students’ conceptualization of ownership and privacy of self-tracking data - Agesilaou, Andria; Kyza, Eleni A. (My University, 2020)
Children are reported to have limited knowledge of where, why and by whom their data are being (re)used. This study examined students’ understanding of personal digital data, and the reasons they are willing to concede personal data ownership. Data were collected from an educational intervention with 63 elementary school students. Results indicate that students’ awareness of the commercial use of their personal data is not well-developed and that ownership of data varies according to context.
Keywords: Computer science; Digital datas; Data ownership; Educational intervention